2022
DOI: 10.2337/dc21-2417
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interventions to Prevent Type 2 Diabetes on the Development of Diabetic Retinopathy: The DPP/DPPOS Experience

Abstract: OBJECTIVE To determine whether interventions that slow or prevent the development of type 2 diabetes in those at risk reduce the subsequent prevalence of diabetic retinopathy. RESEARCH DESIGN AND METHODS The Diabetes Prevention Program (DPP) randomized subjects at risk for developing type 2 diabetes because of overweight/obesity and dysglycemia to metformin (MET), intensive lifestyle intervention (ILS), or placebo (PLB) to as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The clinically relevant information our system contributes to, is to detect people with preventable risk factors for type 2 diabetes. Even though the Diabetes Prevention Program recently reported that interventions that delay the development of type 2 diabetes in those at risk (overweight/obese with dysglycemia) do not reduce the subsequent prevalence of DR [ 97 ], this concerns people who have progressed to diabetes. In cases where intensive lifestyle intervention and metformin managed to prevent progression to type 2 diabetes, DR does not happen [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinically relevant information our system contributes to, is to detect people with preventable risk factors for type 2 diabetes. Even though the Diabetes Prevention Program recently reported that interventions that delay the development of type 2 diabetes in those at risk (overweight/obese with dysglycemia) do not reduce the subsequent prevalence of DR [ 97 ], this concerns people who have progressed to diabetes. In cases where intensive lifestyle intervention and metformin managed to prevent progression to type 2 diabetes, DR does not happen [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the Diabetes Prevention Program recently reported that interventions that delay the development of type 2 diabetes in those at risk (overweight/obese with dysglycemia) do not reduce the subsequent prevalence of DR [ 97 ], this concerns people who have progressed to diabetes. In cases where intensive lifestyle intervention and metformin managed to prevent progression to type 2 diabetes, DR does not happen [ 97 ]. In this regard, it is important to recognize that lifestyle interventions must be carried out with considerable involvement of clinicians and that acheiving awareness among patients and family relatives is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The clinically relevant information our system contributes to is to detect people with high likelihood of preventable risk factors for DR. Even though the Diabetes Prevention Program recently reported that interventions that delay the development of type 2 diabetes in those at risk (overweight/obese with dysglycemia) do not reduce the subsequent prevalence of DR 81 , this concerns people who have progressed to diabetes. In cases where intensive lifestyle intervention and metformin managed to prevent progression to type 2 diabetes, DR does not happen 81 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though the Diabetes Prevention Program recently reported that interventions that delay the development of type 2 diabetes in those at risk (overweight/obese with dysglycemia) do not reduce the subsequent prevalence of DR 81 , this concerns people who have progressed to diabetes. In cases where intensive lifestyle intervention and metformin managed to prevent progression to type 2 diabetes, DR does not happen 81 . In this regard, it is important to recognize that lifestyle interventions must be carried out with considerable involvement of clinicians and that acheiving awareness among patients and family relatives is challenging.…”
Section: Strengths and Interpretation Of Spontaneous Erg Signals' Pre...mentioning
confidence: 99%
“…Regarding eye screening, the role of prevention of ocular pathologies in the general population had been extensively discussed, with a relevant reduction of complications especially in diabetic patients [16,17]. Many studies have previously investigated visual health and visual healthcare access in refugees or displaced persons, with a prevalence of blindness ranging from 1.6 to 26.2% and a high prevalence of ocular infectious diseases such as trachoma [18].…”
Section: Introductionmentioning
confidence: 99%